The Innovation as a Commercial Management Tool in SMEs in Santo Domingo de los Tsáchilas - Erazo-Rivera, Renato Patricio (2021)
The current disruptive scenario in the Ecuadorian economy encourages SMEs to generate innovations in their management models that allow them to obtain competitive advantages. Through this study, it is intended to know, based on a systemic analysis, the degree of adoption of innovation and ICT tools in SMEs in the city of Santo Domingo (Ecuador). For the development of the study, the mixed, qualitative and quantitative methodological approach was used. Through the application of surveys and documentary review, it is possible to assess how entrepreneurs in this city use ICT. The results of the study show little use of existing technology for the development of innovative management strategies, a consequence of the low level of business culture and the risk aversion of entrepreneurs, a result already reported in previous studies.